Answer:
y = -1, x = -2
Step-by-step explanation:
First, multiply the top equation by 2 to make 3x become 6x:
6x - 8y = -4
Second, multiply the bottom equation by 3 to make -2x become -6x:
9y - 6x = 3
Add the two equations together, and you get:
y = -1
Plug in y as -1 into the first or second equation:
3x - 4(-1) = -2
OR
3(-1) - 2x = 1
x = -2
Answer:
i can't answer this but i can tell you this
The general form of an absolute value function is f(x)=a|x-h|+k. From this form, we can draw graphs.
y = a(x – h)2 + k, where (h, k) is the vertex. ... In the vertex form of the quadratic, the fact that (h, k) is the vertex makes sense if you think about it for a minute, and it's because the quantity "x – h" is squared, so its value is always zero or greater; being squared, it can never be negative.
Step-by-step explanation:
it is not the answer but i hope it helps:)
Answer:
what does it look like we need that
Step-by-step explanation:
Let x is the first no. then the other no. will obviously be (x+1)
according to question,
(x+1)²- x²= 15
x² +2x+1 - x² = 15 ( using (a+b)²= a²+ b² + 2ab )
2x + 1 = 15
2x = 14
x = 7
hence numbers are x = 7 and x +1 = 7+1 = 8
also 8²-7² = 64-49 = 15
hence the numbers are 7 and 8
hope it helped
It’s Has to be B because if you had the negative numbers you get -12